2013
DOI: 10.1371/journal.pone.0069120
|View full text |Cite
|
Sign up to set email alerts
|

Association between Interleukin-4 Receptor α Chain (IL4RA) I50V and Q551R Polymorphisms and Asthma Risk: An Update Meta-Analysis

Abstract: BackgroundThe associations between the interleukin-4 receptor α chain (IL4RA) I50V and Q551R polymorphisms and asthma risk remained controversial.MethodsWe searched the Pubmed, Embase, Chinese National Knowledge Infrastructure (CNKI) and Wanfang databases for studies published before February 2013. The strengths of the associations were calculated using odds ratios (ORs) with 95% confidence intervals (CIs).ResultsA total of 50 studies were included in this meta-analysis. There was a significant association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
(22 reference statements)
2
18
0
Order By: Relevance
“…This could suggest that the patient carrying the A allele of IL-4RA-175V had an increased risk for asthma. This data is consistent with previous studies [24,26]. Nevertheless, other studies showed insignificant association of this polymorphism with asthma risk [18].…”
Section: Il-4 Is a Th2 Cytokine That Plays An Essential Role In Ige Rsupporting
confidence: 94%
See 1 more Smart Citation
“…This could suggest that the patient carrying the A allele of IL-4RA-175V had an increased risk for asthma. This data is consistent with previous studies [24,26]. Nevertheless, other studies showed insignificant association of this polymorphism with asthma risk [18].…”
Section: Il-4 Is a Th2 Cytokine That Plays An Essential Role In Ige Rsupporting
confidence: 94%
“…Previous reports have shown that IL-4 C-589T polymorphism influences asthma risk in a most probable dominant model, i.e., one -589T allele has adequate capacity to enhance the asthma risk of susceptible individuals [23]. Also, a previous meta-analysis observed the association between −589C/T polymorphism and asthma among Asians and Caucasians but not among African Americans [26]. Our results go hand in hand with this trend.…”
Section: Il-4 Is a Th2 Cytokine That Plays An Essential Role In Ige Rsupporting
confidence: 78%
“…17 that IL4RA Q551R polymorphism predisposes children but not adults to asthma, and its exact role in the pathogenesis is still not conclusive. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Both interleukin 4 (IL4) and interleukin 13 (IL13) are cytokines produced mainly by T-helper 2 (Th2) cells and they play a crucial role in the pathogenesis of allergic inflammation including allergic asthma [1,2]. Interleukin 4 and interleukin 13 recruit mast cells and eosinophils, induce isotype class-switching of B-cells for IgE synthesis and regulate expression of MHC II, CD23 and VCAM-1 [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In regard to interleukin 4 receptor a chain gene, two functional polymorphisms were reported: rs1805010, observed to cause up-regulation of IL4Ra response to IL4 [17], and rs1805011, which function remains unknown. The former genetic variant was found to be associated with asthma [2,18] and the latter with asthma [14] and atopic dermatitis [19]. In interleukin 13 gene, a functional SNP contributing to aminoacid substitution R110Q (rs20541) was described to change the binding strength of IL13 to its receptor, causing higher activity of Gln110 variant [20].…”
Section: Introductionmentioning
confidence: 99%